KINERJA KEUANGAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) ANTARA PERUSAHAAN BUMN DAN PERUSAHAAN NON BUMN DI INDONESIA - Berliana, Farida; Widarno, Bambang; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to determine differences in financial performance andCSR disclosure between BUMN and Non BUMN companies, also to determine therelationship of financial performance with CSR disclosure. The types of data usedin this study are qualitative and quantitative data. The data source used issecondary data. The population in this study are all BUMN and non BUMNcompanies in Indonesia. The sample used in this study were 20 BUMN companiesand 20 non-BUMN companies. The sampling technique uses purposive samplingwith certain criteria and several considerations. Data analysis techniques used inthis study are descriptive analysis, independent sample t-test, and correlationanalysis. The results of data analysis show that there are no differences infinancial performance between BUMN and Non BUMN companies, there aredifferences in CSR disclosure between BUMN and Non BUMN companies, andhave a very weak positive relationship between financial performance and CSRdisclosure of BUMN and Non BUMN companies.